Small Scale Gas Producer-Engine Systems - Kaupp, Albrecht; Goss, John R. (Vieweg+Teubner Verlag, 1984)
This monograph was prepared for the Agency for International Development, Washington D. C. 20523. The authors gratefully acknowledge the assistance ofthe following Research Assistants in the Department of Agricultural Engineering: G. Lamorey, E. A. Osman and K. Sachs. J. L. Bumgarner, Draftsman for the Department, did most ofthe ink drawings. The writing of the monograph provided an unique opportunity to collect and study a significant part of the English and some German literature on the subject starting about the year 1900. It may be concluded that, despite renewed worldwide efforts in this field, only in significant advances have been made in the design of gas producer-engine systems. Eschborn, February l3, 1984 Albrecht Kaupp Contents Chapter I: Introduction and Summary 1 Chapter II: History of Small Gas Producer Engine Systems 8 Chemistry of Gasification 25 Chapter III: Gas Producers 46 Chapter IV: Chapter V: Fuel 100 Chapter VI: Conditioning of Producer Gas 142 Chapter VII: Internal Combustion Engines 226 Chapter VIII: Economics 268 Legend 277 CHAPTER I: INTRODUCTION Gasification of coal and biomass can be considered to be a century old technology